2019
DOI: 10.1111/corg.12274
|View full text |Cite
|
Sign up to set email alerts
|

Organizational discretion, board control, and shareholder wealth: A contingency perspective

Abstract: Research Question/Issue How does organizational context influence the impact of board control over managerial decisions on shareholder wealth? Research Findings/Insights We introduce a new theoretical concept—organizational discretion—to characterize the upper limit of managers' latitude of actions presented by their organizational context and propose that it moderates the impact of board control on shareholder wealth. Specifically, we first argue that strategic control by boards over managerial decisions redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 89 publications
1
5
0
Order By: Relevance
“…Our findings also contribute to a growing body of research on the organizational identification of firm leaders. A number of empirical studies point to the potential benefits of organizational identification at the executive level, including a reduction in agency costs and a stronger commitment to long‐term strategic goals (Boivie et al, 2011; Moore & Kraatz, 2011; Ponomareva, Shen, & Umans, 2019; Prasad & Junni, 2017). Moreover, scholars have long suggested that high levels of organizational identification should reduce intergroup bias and discrimination within firms, as the organization provides a superordinate category that reduces the salience of intergroup distinctions among its members (Ashforth, Harrison, & Corley, 2008; Kramer, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also contribute to a growing body of research on the organizational identification of firm leaders. A number of empirical studies point to the potential benefits of organizational identification at the executive level, including a reduction in agency costs and a stronger commitment to long‐term strategic goals (Boivie et al, 2011; Moore & Kraatz, 2011; Ponomareva, Shen, & Umans, 2019; Prasad & Junni, 2017). Moreover, scholars have long suggested that high levels of organizational identification should reduce intergroup bias and discrimination within firms, as the organization provides a superordinate category that reduces the salience of intergroup distinctions among its members (Ashforth, Harrison, & Corley, 2008; Kramer, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, public rent-seeking activities could distort resource allocation by increasing the returns to unproductive rent-seeking activities rather than innovative and strategic activities for higher productivity (Baumol, 1990). More recent research (Ponomareva et al, 2019) has shown that while an increase in strategic control by the principal may reduce the costs of managerial opportunism which seeks to promote agents' interest at the expense of shareholders, the increasing constraints on managerial discretion beyond a certain level can significantly reduce a range of managers' strategic decisions and behaviors, rather increasing strategic opportunity costs and leading to decreased organizational performance.…”
Section: Theoretical Backgroundsmentioning
confidence: 99%
“…We thus attempt to answer a question, “Does the effect of managerial discretion on organizational performance change by different levels of discretion?” or “Is the relationship between discretion and organizational performance nonlinear?” Indeed, recent research in business management (e.g. Ponomareva et al, 2019) suggested a curvilinear relationship between managerial discretion and organizational outcomes. A higher level of managerial discretion with little strategic control may lead to higher costs of managerial opportunism at the expense of shareholders’ interests, but decreasing managerial discretion beyond a level which is not acceptable to managers may rather increase strategic opportunity costs, thereby lowering organizational performance (Ponomareva et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The literature on banks' corporate governance is mainly comprised of the assessment of risk-taking and the performance of the banks. Banks' risk-taking comportment varies with the shareholders' discretionary power within the structure of corporate governance of the banks (Laeven & Levine, 2009;Ponomareva et al, 2019;Russino et al, 2019). Moreover, capital reserve requirements and deposit insurance policies depend on the ownership structure of banks.…”
Section: Literature Reviewmentioning
confidence: 99%